Use of the spoken speech in native language from ECCI’s modern languages students (2014)
Spanish as a native language deserves an important place inside the process in Modern Languages students. In order to clarify this aspect about the use or the speech of it as relevant in the major at ECCI, it developed an idea to perceive different opinions and points of view of students according to their training during the final stage of their professional cycle. The participants were the main support to put into practice the qualitative method, where, each category reflected positives aspects related to the native language. These aspects allowed underlining the importance of native language as support to learn a foreign language as well as to improve the curriculum of this major. Additionally the results showed that the students have a big interest for the first language and take a special attention to learn a foreign one.